Ultra-flexible and highly sensitive scintillation screen based on perovskite quantum dots for non-flat objects X-ray imaging. (May 2021) - Xu, Qiang; Zhou, Shuai; Huang, Jie; Ouyang, Xiao; Liu, Jun; Guo, Yong; Wang, Juan; Nie, Jing; Zhang, Xinlei; Ouyang, Xiaoping; Jia, Wenbao
Abstract: A flexible and highly sensitive scintillation screen is urgently expected for X-ray imaging technology, especially for non-flat, flexible objects in medical and industrial applications. Here, we report a sandwich structure of polymer-perovskite quantum dots-polymer (PPP) scintillation screen. The outer polymer layer provides high mechanical stability and encapsulation for the internal perovskite quantum dots active layer. The relative light output remains 93 ± 0.5% of its initial value after bending cycles up to 600 with a bending radius down to 2.5 mm. This PPP scintillation screen exhibits ultra-sensitivity to low energy X-ray with a detection limit of 1.57nGyair /s and fast decay time of 63.7ns. Well-resolved X-ray images are recorded with a common digital camera with a spatial resolution of 5.35 lp/mm at MTF = 0.3 under the exposure dose of 12 μGyair, which is much lower than the requirement of medical applications. These features demonstrate that this flexible scintillation screen can be applied for non-flat X-ray imaging applications under low-dose X-ray exposure. Graphical abstract: Image 1 Highlights: Polymer-Perovskite QDs-Polymer sandwich structure scintillation screen has been synthesized with a simply spin-coated method. Polymer-Perovskite QDs-Polymer thin film exhibits ultra-flexible. Polymer-Perovskite QDs-Polymer thin film exhibits the high sensitivity, fast response and stable to X-ray. High-resolution X-ray imaging is achieved for non-flat objects.